Congresso Paulista de Educação Infantil - COPEDI: contribuições à formação de professoras/es de Educação Infantil (1998-2022) - Araujo, Bruna Paes Junqueira (2023)
The objective of this research was to investigate to what extent the editions of the São Paulo Congress of Early Childhood Education (COPEDI), by bringing current themes in the theory-practice relationship, constitute a training space for early childhood education professionals. It is understood that teacher training, whether initial or continuing, should not be limited to the formal/university space, which, although it is essential, ends up not being enough, since teaching in early childhood education requires a broad and diversified training. In this sense, in addition to the individual dimension, teacher training demands interaction and collectivity, because it is through the interactions between daily practices and knowledge that training is constituted. For Nóvoa (1986, 2013, 2017), teacher training as training for a profession takes place in the crossing of different institutions. And precisely because it is understood that theoretical activity and "isolated" practice do not lead to the transformation of reality, COPEDI is taken as the object of study, a broad and plural space of recognized importance in the national scenario in the area of Early Childhood Education, which brings together teachers, researchers, specialists, students and other subjects interested in debates, research and propositions in relation to childhood. children and their rights and Early Childhood Education. Among the theoretical frameworks, we highlight some authors who served as a basis for the dialogue between teacher training, public policies, early childhood education, education forums and COPEDI: NÓVOA; KRAMER; MORUZZI; ROSENBERG; FARIA and PALHARES; MAUDONNET; SERRAO AND NASCIMENTO; TOMAZZETTI; SANTOS and MELLO. The qualitative research was organized in two complementary stages: a) bibliographic research that aimed to deepen and analyze the accumulated scientific knowledge on the theme of early childhood education teacher training and public policies, in addition to mapping the data around COPEDI and teacher training in the period from 1998 to 2019; b) documentary research, which focused on documents derived from COPEDIs, such as: Annals, programming notebooks, books, and other sources such as websites/online pages of each edition. For the analysis and discussion of the data, publications from the FPEI and MIEIB were taken as a parameter. From the materials studied, some categories of analysis were created. Thus, in the course of the research it was possible to notice the importance and recognition by researchers, students, teachers, of MIEIB, FPEI and COPEDI for the field of early childhood education. The themes of COPEDI are in line with what has been presented in the meetings of WG07 of ANPEd. Broadly speaking. In general terms, it is concluded that although COPEDI is not directly responsible for the training of teachers of early childhood education, it brings contributions to the training of these professionals to the extent that the community fosters debates from the academic sphere, the legal field and the daily practices of early childhood education, in addition to dialoguing with people and institutions directly responsible for initial and continuing education. The survey and analysis of the themes indicate that they arise from pressing situations in each historical, political and social context. Influenced, therefore, by demands brought about by changes in public policies regarding the organization and structuring of early childhood education. On the other hand, COPEDI still has the challenge of expanding the participation of basic education teachers. Keywords: Teacher education. São Paulo Congress of Early Childhood Education. Early Childhood Education. Public policy.